OP0306 Evaluation of Disease Activity Using FDG PET-CT in Patients with Large Vessel Vasculitis. (23rd January 2014) - Pazzola, G.; Magnani, L.; Boiardi, L.; Pipitone, N.; Muratore, F.; Versari, A.; Formisano, D.; Addimanda, O.; Meliconi, R.; Pulsatelli, L.; Bajocchi, G.; Catanoso, M.; et al.
Abstract : Background: 18F-Fluorodeoxyglucose (FDG) positron emission tomography (PET)/computerized tomography (CT) [PET/CT] has been proposed as a useful tool to diagnose and monitor activity of large vessel vasculitis (LVV), but its precise role remains debated. Objectives: To determine the value of PET-CT in the assessment of disease activity in LVV. To this end, PET/CT findings were correlated with clinical indices including ITAS (Indian Takayasu activity score) and Kerr/National Institute of Health (Kerr/NIH), serum acute-phase reactants (ESR, C-reactive protein [CRP]) levels as well as interleukin-6 (IL-6) and the soluble IL-6 receptor (sIL-6R). Methods: 78 patients with LVV (giant cell arteritis, Takayasu arteritis or idiopatic aortitis) underwent a total of 215 PET/CT scans. PET/CT scans were reviewed by a nuclear medicine physician without knowledge of clinical information. Vascular uptake was graded using a 4-point semiquantitative scale. PET/CT scans were considered negative if vascular FDG uptake was grade 0-1, moderately positive if vascular uptake was grade 2, and markedly positive if vascular uptake was grade 3 in at least one vessel. ITAS, Kerr/NIH scores, ESR, CRP, IL-6 and sIL-6R values were obtained within 20 days of PET/CT scans. Results: 43% of 215 PET-CT were negative, 31% were moderately positive, and 26% were markedly positive. We found a significant association between the intensity of the uptake and both ESR and CRP levels. Significantly higher ESR values were observed in the patients with markedly positive PET/CT (49.4 ± 36.5 mm/1st h) compared with those with moderately positive (27± 21 mm/1st h, p = 0.0001) and inactive scans ( 22.7 ± 15.9 mm/1st h, p=0.0001), respectively. CRP levels were 0.8±1.0 mg/dL in patients with inactive scans, 1.3± 2.2 mg/dL in patients with moderately positive (p=0.001) and 3.0 ± 3.6 in patients with markedly positive scans (p = 0.0001). Significantly higher levels of IL-6 were measures in patients with markedly positive scans (10.0 ± 8.9 pg/ml) compared to those with inactive scans (8.1±18.5 pg/ml, p=0.013). No association was found between sIL-6R levels and intensity of vascular FDG uptake. There was a significant association between the intensity of vascular FDG uptake and both ITAS and Kerr/NIH scores. Patients with markedly positive scans had more frequently (50%) active vasculitis according to the ITAS compared with those with moderately active (31.7%) and inactive scans (28.1%) (p=0.003). Likewise, vasculitis was judged to be active according to the Kerr/NIH index in 50% of patients with markedly positive scans, 22% of those with moderately positive scans, and 14.6% with inactive scans (p=0.0001). Conclusions: Our findings show a strong association between vascular FDG uptake and clinical activity and traditional inflammatory markers. A weaker association was found between vascular FDG uptake and IL-6 levels. These data suggest that PET/CT may be a useful tool for evaluating disease activity in patients with LVV. Disclosure of Interest: None Declared